An early experience with Coronary Artery Bypass Surgery: Is there a learning curve for Off Pump Coronary Artery Bypass technique? - Koirala, Ramesh Raj; Pradhan, Siddartha; Acharya, Anil; Sharma, Pramod; Koirala, Bhagwan (Nepalese Heart Journal, 2004)
Ischemic heart disease is a major cause of morbidity and mortality even in Nepal. Data from various clinical trials and retrospective studies suggest that as the number of diseased major coronary arteries increases, the greater the survival benefit of surgical therapy over medical therapy alone.